2023
DOI: 10.1007/s10029-023-02862-4
|View full text |Cite
|
Sign up to set email alerts
|

Drain versus no drain in elective open incisional hernia operations: a registry-based analysis with 39,523 patients

M. Sahm,
M. Pross,
M. Hukauf
et al.

Abstract: Purpose Elective open incisional hernia operations are a frequently performed and complex procedure. Prophylactic drainage is widely practised to prevent local complications, but nevertheless the benefit of surgical drain placement remains a controversially discussed subject. Objective of this analysis was to evaluate the current status of patient care in clinical routine and outcome in this regard. Methods The study based on prospectively collected data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, the function of drains can also be impaired by clotting. Overall, a large registry study demonstrated more complication-related reoperations after drain insertion [32].…”
Section: Discussionmentioning
confidence: 97%
“…However, the function of drains can also be impaired by clotting. Overall, a large registry study demonstrated more complication-related reoperations after drain insertion [32].…”
Section: Discussionmentioning
confidence: 97%
“…This practice, however, has not been particularly well studied in the hernia population. [44][45][46][47][48]. While one recent randomized study demonstrated no difference between the size of residual fluid collection between a drain vs. no-drain group, they also demonstrated a significantly lower complication rate in the drainage group, including less risk of dehiscence [46].…”
Section: Complications Of Mesh Placementmentioning
confidence: 99%